A non-cooperative decentralized model for Volt-VAr optimization of active distribution networks with multiple AC and DC microgrids - Arpanahi, Moossa Khodadadi; Nateghi, Abolfazl; Heydarian-Forushani, Ehsan; Shafie-khah, Miadreza (Elsevier, 2023)
Volt-VAr optimization (VVO) is an important issue for distribution network operators in active distribution networks with a number of AC and DC microgrids. This paper introduces a coordinated decentralized framework with application to Volt-VAr optimization in distribution networks with multiple AC and DC microgrids in the presence of distributed energy resources (DERs). To this end, a non-cooperative coordination model is proposed so that micro-grids operators (MGOs) and distribution system operator (DSO) could minimize their own active power losses, separately. In fact, the DSO and MGOs interact together to achieve an equilibrium that satisfies their expected active power loss. In order to solve the proposed coordinated non-cooperative problem, a novel decentralized optimization approach is suggested so that the master problem is decomposed into two sub-problems from DSO and MGOs point of views. These two sub-problems are linked to each other through sharing boundary information. On this basis, the communicational and computational loads are decreased while information secrecy is guaranteed. The modified IEEE 69-bus distribution network considering a number of AC and DC MGs has been chosen with the aim of conducting several numerical analyses.
Keywords: Volt-VAr optimization; Decentralized optimization; Hybrid AC and DC microgrids; Non-cooperative coordination model; fi=Sähkötekniikka|en=Electrical Engineering|